Government support programmes, business opportunity, and competitive advantage in the halal cosmetic and personal care industry - Muhammad Hafeez, Zakaria (2020)
The Halal Industry Master Plan 2008-2020 reflects the commitment and effort of the Malaysian government to encourage private business enterprises in the halal cosmetic and personal care industry to be more competitive. The private business enterprises are deemed to lack the competitive advantage to compete with international non-certificate halal cosmetic and personal care products. This empirical study was conducted to examine the relationship between government support programmes (contractual programmes and relational programmes) and the competitive advantage of private business enterprises and to measure the mediating effect of business opportunity on the relationship between government support programmes (contractual programmes and relational programmes) and the competitive advantage of private business enterprises in the halal cosmetic and personal care industry. The field work involved 84 respondents consisted of top management in private business enterprises that produce and supply cosmetic and personal care products. There are four hypotheses tested using PLS in this study. This study found mixed findings between government support programmes (contractual programmes and relational programmes) as independent variables and the competitive advantage of private business enterprises as a dependent variable. It is shown that there is a significant positive relationship between contractual programmes and competitive advantage of private business enterprises. The result also showed that there is a negative relationship between relational programmes and competitive advantage of private business enterprises. When business opportunity was included as a mediating variable to test the relationship between contractual programmes and relational programmes and the competitive advantage of private business enterprises, surprisingly, the relationship between contractual programmes and competitive advantage of private business enterprises was not significant. Meanwhile, the relationship between relational programmes and competitive advantage of private business enterprises became positive when business opportunity was added to the model. This study is only focused on the halal cosmetic and personal care industry in Malaysia and it is suggested that future studies may include comparative studies with other halal sectors and focus to see the performance of the halal products in the market segment in other regions in terms of government support programmes.